Formula to estimate left atrial volume using antero-posterior diameter in patients with catheter ablation of atrial fibrillation. Issue 29 (23rd July 2021) - Sangsriwong, Muktapha; Cismaru, Gabriel; Puiu, Mihai; Simu, Gelu; Istratoaie, Sabina; Muresan, Lucian; Gusetu, Gabriel; Cismaru, Andrei; Pop, Dana; Zdrenghea, Dumitru; Rosu, Radu
Abstract : Abstract: In patients undergoing atrial fibrillation (AF) ablation, an enlarged left atrium (LA) is a predictor of procedural failure as well as AF recurrence on long term. The most used method to assess LA size is echocardiography-measured diameter, but the most accurate remains computed tomography (CT). The aim of our study was to determine whether there is an association between left atrial diameters measured in echocardiography and the left atrial volume determined by CT in patients who underwent AF ablation. The study included 93 patients, of whom 60 (64.5%) were men and 64 (68.8%) had paroxysmal AF, who underwent AF catheter ablation between January 2018 and June 2019. Left atrial diameters in echocardiography were measured from the long axis parasternal view and the LA volume in CT was measured on reconstructed three-dimensional images. The LA in echocardiography had an antero-posterior (AP) diameter of 45.0 ± 6 mm (median 45; Inter Quartile Range [IQR] 41–49, range 25–73 mm), longitudinal diameter of 67.5 ± 9.4 (median 66; IQR 56–88, range 52–100 mm), and transversal diameter of 42 ± 8.9 mm (IQR 30–59, range 23–64.5 mm). The volume in CT was 123 ± 29.4 mL (median 118; IQR 103–160; range 86–194 mL). We found a significant correlation ( r = 0.702; P < .05) between the AP diameter and the LA volume. The formula according to which the AP diameter of the LA can predict the volume was: LA volume = AP diam 3 + 45 mL. There is a clear association between the left atrial AP diameter measured on echocardiography and the volume measured on CT. The AP diameter might be sufficient to determine the increase in the volume of the atrium and predict cardiovascular outcomes.